Advancing bibliometric assessment of research productivity: an analysis of US Departments of Family Medicine - Susan M. Dovey; Stephen Petterson; Daniel McCorry; Tanvir Chowdhury Turin; Bernard Ewigman; Andrew W. Bazemore; Winston Liaw (CSIRO Publishing, 2020)
ABSTRACT INTRODUCTIONMeasurement of family medicine research productivity has lacked the replicable methodology needed to document progress. AIMIn this study, we compared three methods: (1) faculty-to-publications; (2) publications-to-faculty; and (3) department-reported publications. METHODSIn this cross-sectional analysis, publications in peer-reviewed, indexed journals for faculty in 13 US family medicine departments in 2015 were assessed. In the faculty-to-publications method, department websites to identify faculty and Web of Science to identify publications were used. For the publications-to-faculty method, PubMed's author affiliation field were used to identify publications, which were linked to faculty members. In the department-reported method, chairs provided lists of faculty and their publications. For each method, descriptive statistics to compare faculty and publication counts were calculated. RESULTSOverall, 750 faculty members with 1052 unique publications, using all three methods combined as the reference standard, were identified. The department-reported method revealed 878 publications (84%), compared to 616 (59%) for the faculty-to-publications method and 412 (39%) for the publication-to-faculty method. Across all departments, 32% of faculty had any publications, and the mean number of publications per faculty was 1.4 (mean of 4.4 per faculty among those who had published). Assistant Professors, Associate Professors, Professors and Chairs accounted for 92% of all publications. DISCUSSIONOnline searches capture a fraction of publications, but also capture publications missed through self-report. The ideal methodology includes all three. Tracking publications is important for quantifying the return on our discipline's research investment.